Mengenal Konflik Akar Penolakan Dan Dampaknya Dalam Membangun Rumah Tangga Kristen - Pangarapen Sembiring (Manna Rafflesia, 2020)
In building a household, conflicts often occur, one of the biggest conflicts heard by marriage counselors in the household is a statement like the following: "My wife really doesn't understand me", or my husband never listens to me. So that makes most of the wavering marriage currently foundered experiencing divorce. Because many couples fail and do not have the ability to understand the roots of rejection experienced by their partners, or do not really know the dark past the partner can also be due to the lack of openness from the couple related to the past in the family of each partner. Negative effects will be seen after a few months or a few years in marriage then comes the original negative nature that causes anger and hatred towards the couple. The problem is not only that the impact of refusal can lead to sexual immorality or live in uncleanness in the household and even many infidelities occur because of dissatisfaction from each partner. The point in building a partner's household is not to be blind to see and pay attention to their partner enough just to fall in love to see the appearance and sympathetic nature and attention shown by their partner, but more importantly we can see the background of the past and are ready to accept all the weaknesses that are owned by his partner and completes and helps both partners to build a harmonious and happy home.